Measurement of Artery Stiffness Index (ASI) using blood volume pulse - Mohamed, A.H.; Moghavvemi, M.; Wan Ibrahim, W.M.A. (2008)
A new approach is studied to detect the artery stiffness index (ASI) and endothelial dysfunction degree by using the blood volume pulse (BVP) during pulsatile cycle. In this approach, the BVP is measured and Fast Fourier Transform (FFT) is used to analyze the plotted signal to its frequency fundamentals. A simple hand made data acquisition system is used to sense the changes in pressure by using the normal Sphygmomanometer device. Six patients are tested, three males and three females. Three of them having hypertension and the rest are healthy control patients. two software programs built using Delphi 2007 language. One to acquire the data from the data acquisition and the second one is to analyze the data. From each patient two waveforms are plotted, the first one after increasing the pressure to 90 mmHg direct, and the second after increasing the pressure above the systolic pressure for 2-3 minutes and then reducing it to 90 mmHg. Analyzing the results shows that there is a major difference between the two graphs in both time and frequency domains.